MUCOLYTICS IN BRONCHOPULMONARY DYSPLASIA THERAPY - I. V. Davydova; T. V. Turti; E. P. Zimina; V. V. Altunin (Педиатрическая фармакология)
Mucolytic drugs, particularly, direct action mucolytics with acetylcysteine derivatives among them, are included in the complex therapy of the bronchopulmonary dysplasia exacerbations. However, data on application effectiveness and safety of such a therapy with chronic bronchopulmonary diseases in children of 0–2 years of age are few and contradictory. The article contains proprietary clinical functional data on application of acetylcysteine in granules for the syrup preparation in the treatment of children bronchopulmonary dysplasia.